The Crisis of Authority and Dignity in the Teaching Profession: A Juridical and Ethical Review within Indonesia’s National Education System - Aspandi, Ade; Syarifudin, Aip; Mustaqimah Hasan Basuni, Kiki; Namira Oktafiandri, Andini; Rizky Susanto, Alfinto (Jurusan Pendidikan Teknik Elektro, 2026)
This study explores the crisis of authority and erosion of professional dignity among teachers in Indonesia through a juridical and ethical lens. This research emphasizes the dissonance between existing legal guarantees and their practical implementation in protecting teachers as professional educators. Using a qualitative method and library research approach, this study examines constitutional, statutory, and regulatory provisions, such as Article 28D paragraph (1) of the 1945 Constitution, Law Number 14 of 2005 on Teachers and Lecturers, Government Regulation Number 19 of 2017, and the Indonesian Teachers’ Code of Ethics. Recent media reports highlighting violence against teachers, defamation cases, and administrative neglect were also analyzed to provide contextual evidence. The findings reveal that the government’s legal protection has been largely normative and declarative, with weak enforcement mechanisms that fail to ensure a sense of security and moral recognition for educators. The teaching profession is facing an internal decline in authority due to social distrust, shifting values in education, and institutional pressure that undermines teachers’ autonomy. This paper concludes that reinforcing juridical protection and revitalizing ethical standards are essential for restoring teachers’ dignity and authority within the national education framework. Collaborative synergy between state institutions, professional organizations, and the community is required to uphold justice, ensure teachers’ well-being, and reaffirm their moral standing as the cornerstone of national education.